Networking of Strategic Partnerships in Higher Education: Prerequisites and Readiness of Universities - Baturina, Olga A. (2020)
The priority task of the modern education system development is the organization of a comprehensive partnership, which, among other things, implies the development of network interactions between the university and various economic entities. In this regard, the need to apply new forms of partnerships is actualized, in which openness and readiness of partners for equal, effective and multilateral interaction is in the first place. However, at present, not all economic entities are ready to implement such a form of partner relations. The article examines the tendency of networking in higher education and the level of their development from the perspective of openness. In this work, we tested the methodology for a university readiness evaluation to form and develop a strategic partnership based on the network approach using the example of leading universities of the Russian Federation.